The ARGO Project: assessing NA-TECH risks on offshore oil platforms. (September 2017) - Capuano, Paolo; Basco, Anna; Ruocco, Angela Di; Esposito, Simona; Fusco, Giannetta; Garcia-Aristizabal, Alexander; Mercogliano, Paola; Salzano, Ernesto; Solaro, Giuseppe; Teofilo, Gianvito; Scandone, Paolo; Gasparini, Paolo
Abstract: Analysis of natural and anthRopoGenic risks on Offshore platforms (ARGO) is a 3-years project, funded by the Italian Ministry of Economic Development. The project, coordinated by AMRA, a permanent Research Centre for the development of innovative technologies applied to environmental problems, aims at providing technical-support for the analysis of natural and anthropogenic risks on offshore oil-platforms. ARGO has developed methodologies for the probabilistic analysis of industrial accidents triggered by natural events (NA-TECH) on offshore platforms. The final analysis of the ARGO Project suggest a constant monitoring of exploitation activity, fluids re-injection and storage using high technology networks.